Precarious work behaviour on career satisfaction / Siti Fazilah Hamid … [et al.] - Hamid, Siti Fazilah; Amir Ishak, Noormala; Hussein, Norashikin; Hussain, Ibiwani Alisa (Penerbit UiTM (UiTM Press), 2018)
The development of information technology, along with globalisation, has changed today’s workplace. The impact of dramatic changes in technology as well as globalisation has led to an increase in precarious work behaviour. There are positive associations between precarious work behaviour and career satisfaction. The literature showed satisfaction with work had exhibited an impressive effect on more worldwide regions, for example, satisfaction with a career. Therefore, this paper reviews the literature on precarious work behaviour on career satisfaction. Data were collected using a questionnaire conducted on online entrepreneurs. The data were analysed using Structural Equation Modelling (SmartPLS) to assess the respondents. Results show that precarious work behaviour has a positive influence on career satisfaction. The findings have implications for increasing our understanding of precarious work behaviour on career satisfaction. Implications and conclusions will highlight the challenges faced by online entrepreneurs.